IMPLEMENTASI EDUCATION MANAGEMENT INFORMATION SYSTEM DALAM PENGELOLAAN DATA PONDOK PESANTREN: STUDI KASUS DI AL-IHSAN APPANANG SOPPENG - Amalia, Rahma; Salman, Salman; Musgamy, Awaliah (Department of Islamic Education Management, 2026)
This study aims to analyze the implementation of the Education Management Information System (EMIS) in data management at the Al-Ihsan Appanang Soppeng Islamic boarding school examining the stages of organization, interpretation, and application and to assess its alignment with the Decree of the Director General of Islamic Education Number 5974 of 2019. Employing a descriptive qualitative approach, the study gathered data through semi-structured interviews with an operator, two teachers, and two students. The results indicate that the EMIS implementation complies with government policy and yields benefits such as administrative orderliness, data transparency, and streamlined reporting, while also positively impacting students. Consequently, the system requires support through infrastructure upgrades, the addition of operators, and continuous training for both operators and teachers to ensure that evidence-based Islamic education data management operates more optimally and sustainably.